PENINGKATAN KREATIVITAS DAN KOMUNIKASI SISWA ABAD 21 PADA MATERI BANJIR MELALUI MODEL PBL - Nurpratama, Regita; Subarjah, Herman; Sujana, Atep (Jurnal Pena Ilmiah, 2019)
Creativity and communication are skills that must be possessed by students, especially in the 21st century which requires students to always be active in learning activities. The purpose of this study was to determine the effect of PBL learning models on improving student creativity and communication in flood material. The method used in this study was quasi-experimental with nonequivalent control group design. The population in this study were all fifth grade students in Kecamatan CimalakaÂ  with the samples used were fifth grade students of SDN Cilimbangan as the experimental class and the fifth grade students of SDN Citimun II as the control class. The instruments used in this study were questions of creative thinking ability tests, creative attitude questionnaires, communication assessment rubrics, observation sheets and student response questionnaires. The conclusions obtained from this study are: 1) Learning using PBL models on flood material can improve the creativity ability of students in the experimental class, 2) Learning to use expository on flood material can improve the creativity ability of students in the control class, 3) Students' creativity ability in the experimental class and in the control class are relatively similar, 4) PBL models can significantly improve students' communication skills.